Cost patterns of care for patients with ischemic heart disease at the Instituto Nacional Cardiovascular, 2019 - Sanabria-Montañez, César (2022)
Introduction. Ischemic heart disease (IHD) is currently a public health problem in Peru, and its treatment tends to be very expensive for the health system. Goal. Establish the patterns of care costs of the EIC in the National Cardiovascular Institute (INCOR) of the Social Security in Health of Peru (EsSalud). Methods. The databases of care, surgeries, discharges and gross value of INCOR production of the population diagnosed and treated with IHD in 2019 (879 patients) were used. Costs of care were estimated using activity-based costing; an econometric model was used to establish the determinants of costs, and with the Euclidean distance method, “clusters” with similar characteristics were formed to establish cost patterns. Results. The highest cost of EIC care was 148 567 soles (US$ 44 830) for a patient with a 40-day stay. The main determinants of the cost of care were the hospital stay and the number of admissions to the establishment. It was identified that the “clusters” that had a higher cost were patients with a median age of 70 and 72 years, with a high number of days of stay and with some highly complex surgery. Conclusion. Cost patterns for IHD care were associated with length of stay and readmissions to the health facility. The “clusters” with the highest cost were related to age and complexity of the surgery.